Synthesis and Characterization of Antibacterial ZnO - Functionalized Polysulfone Membrane - Ribka Rumintang; Rinaldi Medali Rachman (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2022)
Membrane technology is an emerging alternative in water treatment. This study aims to synthesize a filtration membrane made of polysulfone polymer with the addition of ZnO in order to enhanced the membrane antibacterial/antibiofouling property. The membrane was manufactured via Non-Induced Phase Separation (NIPS) phase inversion of the polymer casting solution. The composition of ZnO was varied into 0%, 0.5%, 1%, 2%, and 3%. The results of the membrane synthesis were characterized using Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscope (SEM), pure water permeability test, and selectivity test with a turbid meter. The hydrophilic properties of the membrane were analysed by measuring the contact angle, and the antibacterial characteristics were analyzed by the disc diffusion test. Analysis by FTIR showed the presence of a sulfone functional group (S=O) derived from polysulfone polymer and a methyl functional group (C-H) derived from PEG. SEM analysis showed that each variation of the polysulfone membrane had an upper surface structure that was close to the honeycomb structure. The pure air permeability test shows that the membrane is porous and able to pass through pure air. Selectivity test with a turbid meter showed that the membrane is selective to the feed stream that passes through it. Analysis of contact angle measurements showed that the polysulfone membrane surface was hydrophilic. Antibacterial activity analysis showed that polysulfone membrane had antibacterial ability with the largest zone of inhibition with a value 1.8 mm on the membrane with the largest concentration of ZnO.